2013
DOI: 10.3109/10715762.2013.779373
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with cardiovascular disease and chronic renal failure

Abstract: Oxidative response regulates many physiological response in human health, but if not properly regulated it could also lead to a number of deleterious effects. The importance of oxidative stress injury depends on the molecular target, the severity of the stress, and the mechanism by which the oxidative stress is imposed: it has been implicated in several diseases including cancer, neurodegenerative diseases, malaria, rheumatoid arthritis and cardiovascular and kidney disease. Most of the common diseases, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
90
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 100 publications
2
90
0
8
Order By: Relevance
“…There are indeed studies indicating that, under several pathological conditions, certain mechanisms that compensate deficient NO production may be activated [25,28,45]. In particular, these mechanisms include plasma oxidative stress, a condition existing in uremia [46,47], which can cause a paradoxical increase in RBC-NOS activity [48]. In addition, shear stress, by increasing Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…There are indeed studies indicating that, under several pathological conditions, certain mechanisms that compensate deficient NO production may be activated [25,28,45]. In particular, these mechanisms include plasma oxidative stress, a condition existing in uremia [46,47], which can cause a paradoxical increase in RBC-NOS activity [48]. In addition, shear stress, by increasing Ca 2?…”
Section: Discussionmentioning
confidence: 99%
“…The excess amount of these unpaired electrons destroys cellular lipids, proteins, and nucleic acids that have a role in different biological processes (Pruchniak et al 2016). However, the overproduction of reactive oxygen species accelerates the incidence or complications of disorders for example diabetes mellitus, cardiovascular diseases, diabetic nephropathy, Alzheimer's disease, and Parkinson's disease (Popolo et al 2013). Several studies have shown the correlation between oxidative stress and the pathogenesis of both major types of diabetes as well as the development of diabetic complications (Yang et al 2011, Giacco & Brownlee 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The animals were placed in a heated chamber at an ambient temperature of 30-34 °C for 15 min and blood pressure values (1)(2)(3)(4)(5)(6)(7)(8)(9) were recorded for each animal. The lowest three readings were averaged to calculate the mean blood pressure.…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…Increased levels of reactive oxygen species such as superoxide anion, hydrogen peroxide and lipid peroxides are reported in patients with hypertension [3,4]. Arterial hypertension is often associated with pathologies related with oxidative stress and may be considered as a result of systemic damage in different target organs or tissues induced by free radicals [5,6]. Angiotensin Converting Enzyme (ACE) inhibitors have taken their place in clinical use as effective and safe antihypertensives and vascular protective agents [7].…”
Section: Introductionmentioning
confidence: 99%